Optimizing Confiscation of Assets in Accelerating the Eradication of Corruption - Danil, Elwi; Kurniawan, Iwan (Hasanuddin Law Review, 2017)
Nowadays, corruption is still the most and biggest problem facing by Indonesian, due to its impacts on the nation. It caused huge loss to the state finance and even to the democratic life in this country. Various efforts have been resorted to fight corruption, but the results are unfruitful. Until recently, Indonesia is still the third most corrupt country in Asia according to the survey of Transparency International Indonesia (TII) in 2015, with the Corruption Perceptions Index of 36 points. The fight in eradicating corruption cannot be separated from the effort to deter the criminals through severe punishment. However, ICWâs most recent data shows otherwise. During the first half of 2014, there were 261 accused of corruption, with 242 of them were convicted guilty by the Corruption Courts. Among them, 193 were sentenced lenient (between 1-4 years imprisonment), 44 moderate (4-10 years), and only 4 with over 10 years imprisonment. The average length of sentence is therefore 2,9 years. The lenient sentence can also be found in criminal restitution. Only in 87 of the total cases state compensation is imposed, amounting 87.04 billion rupiahs in total. The amount is only 0.022% of the total financial loss of 3.863 trillion rupiahs. The weak penalty triggered then the idea of impoverishing corruptors as a strategic step to accelerate the eradication of corruption while restoring the loss to the state. In contrast to the criminal restitution, which is restricted only to the state loss caused by the perpetrators, criminal confiscation of assets has no limit in amount.